Energy Efficient Routing and Peer to Peer Trust Assessment for Increasing the Network Life Time in Delay Tolerant Networks - Murugaveni, S; Priyalakshmi, B; Vijayan, K (International Journal of Engineering and Technology, 2018)
In military network environments is resource-constrained arrange conditions, where end-to-end network is not ensured because of successive deferral, an efficient solution is required for trustful and energy efficient routing. Proposed work, provenance trust based routing is combined with energy efficient route to opt for a high network lifetime. Proposed scheme is designed for peer-to-peer trust assessment and maximize the delivery of correct messages received by destination nodes while minimizing message delay and communication cost Provenance alludes to the historical backdrop of responsibility for esteemed data. Proposed scheme avoids malicious node using provenance model and achieves good network lifetime using energy efficient routing strategy. Nodeâ€™s trust is calculated dynamically in response to changes in the environmental and node conditions. Â Â